2022
DOI: 10.1002/jcla.24311
|View full text |Cite
|
Sign up to set email alerts
|

Combined diagnosis of QF‐PCR and CNV‐Seq in fetal chromosomal abnormalities: A new perspective on prenatal diagnosis

Abstract: Objective This study aimed to evaluate the effect of QF‐PCR and CNV‐seq in diagnosing prenatal fetal chromosomal aberrations, explore the advantages and necessity of multimethod joint diagnosis. Methods We chose pregnant women with the indication of fetal chromosome examination in our hospital last year, collected 657 cases of amniotic fluid for QF‐PCR and CNV‐seq analyzes. Results While detecting aneuploidy, the coincidence rate of QF‐PCR and CNV‐seq was 100% (56/56). For all 46 chromosomes, 523 cases (79.60%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…33 Some scholars combined CNV-seq with QF-PCR to improve the detection rate of chromosomal abnormalities in prenatal diagnosis and concluded that this combination may be considered as the first-line method of prenatal chromosomal diagnosis. 34,35 The most frequent copy number variation revealed by our meta-analysis was Xp22.31 deletion. X-linked ichthyosis, which caused by the deletion of steroid sulfatase in Xp22.31., is a common recessive genetic disease characterized by generalized dryness and scaling of the skin.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…33 Some scholars combined CNV-seq with QF-PCR to improve the detection rate of chromosomal abnormalities in prenatal diagnosis and concluded that this combination may be considered as the first-line method of prenatal chromosomal diagnosis. 34,35 The most frequent copy number variation revealed by our meta-analysis was Xp22.31 deletion. X-linked ichthyosis, which caused by the deletion of steroid sulfatase in Xp22.31., is a common recessive genetic disease characterized by generalized dryness and scaling of the skin.…”
Section: Discussionmentioning
confidence: 74%
“…Quantitative fluorescence polymerase chain reaction (QF‐PCR) makes use of the amplification of selected short tandem repeats (STRs) sites and quantitative analysis of the allelic dosage ratios to evaluate the numbers of copies of specific chromosomes, so it could find the MCC, some euploidies, and some common aneuploidies 33 . Some scholars combined CNV‐seq with QF‐PCR to improve the detection rate of chromosomal abnormalities in prenatal diagnosis and concluded that this combination may be considered as the first‐line method of prenatal chromosomal diagnosis 34,35 …”
Section: Discussionmentioning
confidence: 99%
“…Generally, when copy number (CN) > 2.8, duplication was de ned. Deletion was de ned when CN < 1.2 and disomy (1.8 < CN < 2.2) [15]. The sequencing reads were referred to the Genome Reference Consortium Human genome build 37 (GRCh37) or humangenome 19 (hg19).…”
Section: Case Presentationmentioning
confidence: 99%
“…Through whole genome low-coverage sequencing, CNV-seq is able to detect genetic aberrations, including chromosome aneuploidies and CNVs larger than 100 kb 8 . Combined with the advantages of using small amounts of genomic DNA and detecting low-level mosaicism, CNV-seq has been used increasingly widely for prenatal diagnosis 9 12 . However, due to its low sequencing depth, CNV-seq cannot detect balanced karyotypic changes and polyploidies such as 69, XXX 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, CNV-seq is usually performed in combination with karyotyping or QF-PCR for prenatal diagnosis 9 , 11 , 13 . Karyotyping, the gold standard for detecting chromosome abnormalities, has been used for prenatal diagnosis since the 1960s 14 .…”
Section: Introductionmentioning
confidence: 99%